2011
DOI: 10.1029/2011wr010446
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dynamically variable saturation and matrix‐conduit coupling of flow in karst aquifers

Abstract: [1] Well-developed karst aquifers consist of highly conductive conduits and a relatively low permeability fractured and/or porous rock matrix and therefore behave as a dualhydraulic system. Groundwater flow within highly permeable strata is rapid and transient and depends on local flow conditions, i.e., pressurized or nonpressurized flow. The characterization of karst aquifers is a necessary and challenging task because information about hydraulic and spatial conduit properties is poorly defined or unknown. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…Distributed karst modelling approaches are able to simulate groundwater levels on a spatial grid but their data requirements mostly limit them to theoretical studies (e.g. Birk et al, 2006;Reimann et al, 2011) or well explored study sites (e.g. Hill et al, 2010;Jackson et al, 2011;Oehlmann et al, 2015).…”
Section: S Brenner Et Al: Process-based Chalk Groundwater Modellingmentioning
confidence: 99%
“…Distributed karst modelling approaches are able to simulate groundwater levels on a spatial grid but their data requirements mostly limit them to theoretical studies (e.g. Birk et al, 2006;Reimann et al, 2011) or well explored study sites (e.g. Hill et al, 2010;Jackson et al, 2011;Oehlmann et al, 2015).…”
Section: S Brenner Et Al: Process-based Chalk Groundwater Modellingmentioning
confidence: 99%
“…For this reason, transient water storage can be considered by the continuum model only. Following this, Reimann et al (2011) presented a discrete-continuum modeling approach to simulate unsteady discrete flow in a variably filled pipe network employing the Saint-Venant equations, while de Rooij (2008) and de Rooij et al (2013) additionally considered surface flow and variably saturated matrix flow. The approach appears to be suitable for fundamental studies but high parameter demand and computational effort can be identified as potential drawbacks.…”
Section: T Reimann Et Al: Representation Of Water Abstractionmentioning
confidence: 99%
“…Flow through localized karst conduits might be highly transient, i.e. the application of open channel flow approaches would be appropriate (Reimann et al, 2011a). However, these approaches increase the number of calibration parameters and require additional knowledge about the geometry of a karst conduit system.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the final spring discharge is then a function of the individual flow contributions of each of these compartments (Smart and Hobbs, 1986), which makes the inverse analysis of spring discharge a major challenge, requiring elaborate modeling tools and a large spectrum of data to constrain the model. The simulation of coupled saturated and unsaturated flow is still a challenge in hydrogeology in particular in fractured (Therrien and Sudicky, 1996) and karstified systems (Reimann et al, 2011a). This is predominantly a result of the data scarcity respecting the hydraulic parameter field of real karst systems.…”
Section: Introductionmentioning
confidence: 99%